Dedollarization - Kokenyne, Annamaria (IMF Working Papers; Working Paper ;, 2010)
This paper provides a summary of the key policies that encourage dedollarization. It focuses on cases in which the authorities' intention is to gain greater control of monetary policy and draws on the experiences of countries that have successfully dedollarized. Unlike previous work on the subject, this paper examines both macroeconomic stabilization policies and microeconomic measures, such as prudential regulation of the financial system. This study is also the first attempt to make extensive use of the foreign exchange regulation data reported in the IMF's Annual Report on Exchange Arrangements and Exchange Restrictions. The main conclusion is that durable dedollarization depends on a credible disinflation plan and specific microeconomic measures.